2023
DOI: 10.1002/smll.202207140
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically and Electrically Responsive Soft Actuator Derived from Ferromagnetic Bimetallic Organic Framework

Abstract: The advancement in smart devices and soft robotics necessitates the use of multiresponsive soft actuators with high actuation stroke and stable reversibility for their use in real‐world applications. Here, this work reports a magnetically and electrically dual responsive soft actuator based on neodymium and iron bimetallic organic frameworks (NdFeMOFs@700). The ferromagnetic NdFeMOFs@700 exhibits a porous carbon structure with excellent magnetization saturation (166.96 emu g−1) which allows its application to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Both Al‐fumarate and MIL‐88A belong to the monoclinic space group P 2/ c (Figures S1 and S2, Supporting Information), relying on the similar molecular structure properties , Al and Fe ions can freely adjust the overall topology structure of MOF through the mutual substitution of metal centers. [ 11,33 ] As shown in the field‐emission scanning electron microscope (FESEM) images in Figure 1a,b, the micromorphology of Al‐fumarate and MIL‐88A was found to assemble popcorn‐like and rice‐like structures, respectively. Once Fe atoms and Al atoms are introduced to co‐construct a crystal system, the morphology of each BMOF formed by different Al/Fe ratios changes significantly (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Both Al‐fumarate and MIL‐88A belong to the monoclinic space group P 2/ c (Figures S1 and S2, Supporting Information), relying on the similar molecular structure properties , Al and Fe ions can freely adjust the overall topology structure of MOF through the mutual substitution of metal centers. [ 11,33 ] As shown in the field‐emission scanning electron microscope (FESEM) images in Figure 1a,b, the micromorphology of Al‐fumarate and MIL‐88A was found to assemble popcorn‐like and rice‐like structures, respectively. Once Fe atoms and Al atoms are introduced to co‐construct a crystal system, the morphology of each BMOF formed by different Al/Fe ratios changes significantly (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] However, some challenges remain to be addressed including lack of stable operation in complex environments, low intelligence integration, poor autonomous movement, etc. [20][21][22] Even so, ionic soft actuators, which have the distinct characteristics of controlled driving and fast response under ultra-low voltage, offer a lot of potential in flexible intelligent device applications compared to other similar actuators. Furthermore, traditional expensive and easily cracked precious metal electrode materials are difficult to meet the requirements of new ISAs.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being inexpensive and having high durability, CBNs also have a more straightforward production method that makes it easier to prepare ISAs. [17,46,47] So far, electrode materials of ISAs are more complex and abundant including MoS 2 nanosheets, [85] MXene, [86] metalorganic frameworks (MOFs), [7,21,87] covalent organic frameworks (COFs), [10] CBNs, [88] etc. Compared with other electrode materials, the carbon element of CBNs is abundant in nature, stable, and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24−26 The device exhibited a fast strain rate (2.8% s −1 at 10 Hz) and good blocking force (0.62 mN at 0.1 Hz) at 3 V. 27 Oh et al reported a series of actuator works about PEDOT:PSS-MOF composite material systems, which exhibit outstanding electromagnetic dual response characteristics. 28− 30 Zhang and coworkers reported a core/shell electrode architecture through the radial growth of conductive metal−organic framework (MOF) nanowire arrays around carbon nanofibers. The presence of numerous active surface sites is beneficial to both electron transfer and ion diffusion, resulting in a large driving displacement (12.1 mm), a high strain (0.36%), and broadband frequency response (0.1−20 Hz) at 3 V. 31 Despite most studies having focused on the advantages of the complex hierarchical structures of composite electrodes, the roles of specific dimensions of materials in terms of ion storage space, charge path, and mechanical strength have seldom been investigated.…”
Section: ■ Introductionmentioning
confidence: 99%